Evaluasi Ketersediaan Obat Instalasi Farmasi Rumah Sakit Islam PKU Muhammadiyah Palangka Raya: Evaluation of the Availability of Medicines for the Pharmacy Installation of PKU Muhammadiyah Palangka Raya Islamic Hospital - Guntur Satrio Pratomo; Agustinawati Umaternate; Tiara Febriani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Health services quality is one manifestation of the demands of society in the current era of globalization so it must be carried out in accordance with the established code of ethics and health service standards, in order to provide satisfaction for each patient. In addition, this is very necessary because it is the right of every customer so that it can provide an opportunity for health service facilities to win the competition by providing other health services. The purpose of this study is to determine the level of availability of prescribed drugs for outpatient in pharmacy installation of PKU Muhammadiyah Islamic Hospital Palangka Raya in August to December 2017. This research is a non-experimental study using a descriptive method. Based on the results of the research conducted at the Pharmacy Installation of PKU Muhammadiyah Islamic Hospital Palangka Raya there were 4,956 prescription sheets with an average number of items of 3,035 prescribed drugs and 2,975 items of drugs submitted to obtain the average percentage of drug availability in the year 2017 is 98.02%. Based on the results of research conducted at the Pharmacy Installation of PKU Muhammadiyah Islamic Hospital Palangka Raya, it can be concluded from this study that the level of drug availability for outpatients of Pharmacy Installation at PKU Muhammadiyah Islamic Hospital Palangka Raya in August to December 2017 has shown well with an average percentage of drug availability of 98.02%.